WOMEN’S LANGUAGE AS THE MAIN CHARACTER IN JANE AUSTEN’S NOVEL: PRIDE AND PREJUDICE - Murdianti Murdianti; Muhammad Natsir (LINGUISTICA, 2013)
ABSTRACT This study deals with women’s language analysis on the main character in JaneAusten’s novel: Pride and Prejudice. The objectives of the study are to describe the types of women’s linguistics features on the main character in JaneAusten’s novel Pride and Prejudice, to derive women’s linguistics features on the main character in JaneAusten’s novel Pride and Prejudice, to reason women’s linguistics features on the main character in JaneAusten’s novel Pride and Prejudice. The research was conducted by descriptive qualitative. Thedata are the speech on the main character in JaneAusten’s novel, the data were collected from 1 novel, Pride and Prejudice that has women’s linguistics features.  The data were analyzed by identifying and classifying the figures of speech displaying the result in a table. Then these linguistics features are described in details. The analysis found that there are 9 types of women’s linguistics features which used: lexical hedges is amount 10,06%, tag question is 0,62%, rising intonation on declarative is 2,51%, empty adjective is 3,14%, precise color terms is 0%, intensifier is 56,60%, hyper correct grammar is 1,88%, super polite form is 0,62%, avoidance of swear word is 14,46%, and emphatic stress is 10,06%. The most dominant feature that used is intensifier and the lowest is precise color terms because it is not used in the data. Keywords: Linguistics, Sociolinguistics, Women’s Language